2018
DOI: 10.1016/j.enbuild.2017.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of energy performance and thermal comfort throughout building design process

Abstract: In a traditional building design process (TDP), design variables are fixed sequentially, as opposed to integrated design process (IDP) which tends to avoid sequential design phases to create more sustainable buildings. First, a reference building is introduced and an energy model based on TRNSYS is presented to determine the energy consumption and comfort in the building. The model is validated based on energy bills, certified simulations and literature. Then, the paper performs an extended sensitivity analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Optimal window design attributes have been plotted using parallel coordinates to display a clear design trade-off, see Figure 15, where solution A, B, C and D are represented using different colours. An illustrative design of each optimal solution was reinstated in the case study model, and Revit Insight [87] was used to run an energy simulation to validate each scenario. The energy simulation results have been displayed in Figure 16.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal window design attributes have been plotted using parallel coordinates to display a clear design trade-off, see Figure 15, where solution A, B, C and D are represented using different colours. An illustrative design of each optimal solution was reinstated in the case study model, and Revit Insight [87] was used to run an energy simulation to validate each scenario. The energy simulation results have been displayed in Figure 16.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The energy simulation results have been displayed in Figure 16. An illustrative design of each optimal solution was reinstated in the case study model, and Revit Insight [87] was used to run an energy simulation to validate each scenario. The energy simulation results have been displayed in Figure 16.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The importance of each parameter helped designers to make decisions in the latter stage. Nguyen and Reiter (2015), Rivalin et al (2018) and Gagnon, Gosselin, and Decker (2018) compared several SAtechnics applied to building energy performance assessment. Linear regression was reported not good enough by most researchers.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In Ref. [6], Gagnon et al have used sensitivity analysis techniques to observe the influence of design variables on building performance over the different stages of a design process. The results showed that fixing variables in the early stage reduces the probabilities of finding low-energy consumption designs in the end.…”
Section: Influence Of Design Process On Building Performancementioning
confidence: 99%